2022
DOI: 10.1186/s43141-022-00406-4
|View full text |Cite
|
Sign up to set email alerts
|

In vitro propagation for conservation and genetic fidelity of the near threatened Dimocarpus longan plant

Abstract: Background Dimocarpus longan is a tropical tree that produces edible fruit. It is a neglected plant species that is listed as near threatened. In spite of its economic value, the propagation of longan cultivar using conventional methods is extremely difficult. The goal of this research is to produce and conserve this plant through in vitro propagation. Results In order to form new shoots, sterilized shoot tip explants were cultured on Murashige and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 76 publications
(67 reference statements)
0
2
0
Order By: Relevance
“…Plant tissue culture technology is now becoming an important tool for the largescale production of plant species that have medicinal importance and are generally difcult to cultivate [8]. In addition, the in vitro method can multiply this species because it produces genetically comparable plants quickly and can aid in the recovery of rare endangered threatened (RET) Himalayan herbs [80,[87][88][89]. Recently, a procedure using thin cell layer culture and in vitro plant regeneration through direct somatic embryogenesis for this species were described [90,91].…”
Section: In Vitro Micropropagationmentioning
confidence: 99%
“…Plant tissue culture technology is now becoming an important tool for the largescale production of plant species that have medicinal importance and are generally difcult to cultivate [8]. In addition, the in vitro method can multiply this species because it produces genetically comparable plants quickly and can aid in the recovery of rare endangered threatened (RET) Himalayan herbs [80,[87][88][89]. Recently, a procedure using thin cell layer culture and in vitro plant regeneration through direct somatic embryogenesis for this species were described [90,91].…”
Section: In Vitro Micropropagationmentioning
confidence: 99%
“…However, it was at par with 0.1 mg/l+0.02 mg/l, 0.2 mg/l+0.01 mg/l, 0.1 mg/l+0.01 mg/l, 0.05mg/l+0.005 mg/l and control. According to Ahmed (2022). Danu et al (2015) showed that the combination of GA 3 and IBA increased the sprouting and rooting percentage in Paris polyphylla but at high concentration.…”
Section: Root Lengthmentioning
confidence: 99%